Inverted Oligo‐Miocene metamorphism in the Lesser Himalaya Sequence, Arunachal Pradesh, India; age and grade relationships. (11th July 2016) - Clarke, G. L.; Bhowmik, S. K.; Ireland, T. R.; Aitchison, J. C.; Chapman, S. L.; Kent, L.
Abstract: The Lesser Himalaya sequence in the Siyom Valley, eastern Arunachal Pradesh, exposes a telescoped and inverted greenschist–upper amphibolite facies sequence over ~20 km, tectonically overlain by an upright (grade decreasing upward) granulite to lower amphibolite facies sequence over ~ 30 km. Such grade relationships would normally attribute the boundary to a Main Central Thrust (MCT) structure, and predict a change from underlying Lesser Himalaya Sequence (LHS) to Greater Himalaya Sequence rocks across the boundary. However, all pelitic and psammitic samples have similar detrital‐zircon age spectra, involving c . 2500, 1750–1500, 1200 and 1000 Ma Gondwanan populations correlated with the LHS. Isograds are broadly parallel to a penetrative NW‐dipping S2 foliation, developed contemporaneously with the inversion. Garnet growth in garnet, staurolite and kyanite‐zone schists beneath the thrust commenced at >8 kbar and ≈550 °C, before syn‐ to post‐S2 heating of staurolite and kyanite‐zone rocks to ≈640 °C at ≈8.5 kbar, most probably at c . 18.5 Ma. Kyanite‐rutile‐garnet migmatite immediately above the thrust records peak conditions of ≈10 kbar and ≈750 °C and c.  21.5 Ma monazite ages. Slip on a SE‐propagating thrust was likely contemporaneous with early Miocene metamorphism, based on the distribution of structure, metamorphic textures, and overlap of age relationships. It is inferred to have initially controlled the uplift of granulite to mid‐crustal levels between 22 and 19 Ma, thermal relaxation within a disrupted LHS metamorphic profile inducing a post‐S2 thermal peak in lower grade footwall rocks.